Trades about to happen : a modern adaptation of the Wyckoff method - Weis, David H. (Hoboken, New Jersey : John Wiley & Sons, 2013)
The definitive book on adapting the classic work of Richard Wyckoff to today's markets Price and volume analysis is one of the most effective approaches to market analysis. It was pioneered by Richard Wyckoff, who worked on Wall Street during the golden age of technical analysis. In Trades About to Happen, veteran trader David Weis explains how to utilize the principles behind Wyckoff's work and make effective trades with this method.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Wyckoff, Richard Demille, -- 1873-1935.; Wyckoff, Richard Demille, -- 1873-1935.; Wyckoff, Richard Demille, -- 1873-1935.; Stocks -- Charts, diagrams, etc; Stock price forecasting; Investment analysis; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investment analysis; Stock price forecasting; Stocks; Electronic books; Charts, diagrams, etc; Electronic books